2008
DOI: 10.1055/s-2008-1078420
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Sulfonylation of Arylboronic Acids in Ionic Liquids

Abstract: Cupric acetate in ionic liquids (ILs) catalyzes coupling reaction of arylboronic acids with sulfinic acid salts to afford aryl sulfones in good yields under ambient conditions. This mild and efficient cross-coupling reaction gives access to a wide range of alkylaryl and diaryl sulfones in good yields. The use of ionic liquid allows for easy separation of the product and recycling of copper catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Similarly, Cu-catalyzed coupling of arylboronic acids with sulfinate anions has been reported [95,149,150]. Notably, Kantam and co-workers found that the use of ionic liquids permits Cu(OAc) 2 -catalyzed sulfone synthesis at ambient temperature and with convenient product separation and catalyst recyclability (17) [150]. …”
Section: Equation 16mentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, Cu-catalyzed coupling of arylboronic acids with sulfinate anions has been reported [95,149,150]. Notably, Kantam and co-workers found that the use of ionic liquids permits Cu(OAc) 2 -catalyzed sulfone synthesis at ambient temperature and with convenient product separation and catalyst recyclability (17) [150]. …”
Section: Equation 16mentioning
confidence: 97%
“…More recently, both Cu-and Pd-catalyzed couplings of sulfinate anions with aryl halides have also been reported as a means to generate unsymmetrical diaryl sulfones, which are common motifs in bioactive molecules [38,93,[144][145][146][147][148]. Similarly, Cu-catalyzed coupling of arylboronic acids with sulfinate anions has been reported [95,149,150]. Notably, Kantam and co-workers found that the use of ionic liquids permits Cu(OAc) 2 -catalyzed sulfone synthesis at ambient temperature and with convenient product separation and catalyst recyclability (17) [150].…”
Section: Equation 16mentioning
confidence: 98%
See 1 more Smart Citation
“…Urea-hydrogen peroxide in the presence of catalytic amount of magnesium bromide efficiently oxidizes primary and secondary benzylic alcohols into the corresponding aromatic aldehydes and ketones [30] [34]. M. L. Kantam et al described copper-catalyzed cross-coupling reaction of arylboronic acids with sulfonic acid for alkylaryl and diaryl sulfones using IL [35].…”
Section: Ionic Liquids (Ils)mentioning
confidence: 98%
“…In ionic liquid it was possible to carry out oxidative coupling of aryl boronic acid with the sodium salt of sulfonic acid (Scheme 3.53) [92].…”
Section: Catalytic Cross-coupling Reactions J87mentioning
confidence: 99%